2010
DOI: 10.1038/jp.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical anesthesia and age on pain scores during retinopathy of prematurity screening

Abstract: Objective: The efficacy of topical anesthesia during retinopathy of prematurity (ROP) screening has been a controversial issue. To determine the efficacy of proparacaine eye drops (0.5%), we compared the Premature Infant Pain Profile (PIPP) scores in 40 preterm infants undergoing ROP screening.Study Design: Prospective randomized double masked cross-over clinical trial. The study was conducted in the neonatal intensive units for infants undergoing routine ROP screening exams. Baseline PIPP scores and post-exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Mehta and colleagues 18 compared the response of infants at 2 age points (33.3 and 35.3 weeks) and 2 examination time points (1 and 5 minutes). 18 At the first examination, the PIPP score was significantly lower in the treated group at 1 and 5 minutes, but at the second examination, the PIPP score was lower than at the first examination in both patients and control patients. As a result of the lower overall scores at the second examination, there was no significant difference between treated and control groups.…”
Section: Topical Anesthesiamentioning
confidence: 67%
See 1 more Smart Citation
“…Mehta and colleagues 18 compared the response of infants at 2 age points (33.3 and 35.3 weeks) and 2 examination time points (1 and 5 minutes). 18 At the first examination, the PIPP score was significantly lower in the treated group at 1 and 5 minutes, but at the second examination, the PIPP score was lower than at the first examination in both patients and control patients. As a result of the lower overall scores at the second examination, there was no significant difference between treated and control groups.…”
Section: Topical Anesthesiamentioning
confidence: 67%
“…Table 1 [16][17][18][19] compares 4 different controlled studies of the effects of topical proparacaine on pain relief in premature infants during ROP examinations. In an earlier study of 42 patients, Saunders and colleagues 16 showed no advantage over saline eye drops; however, that study used no standardized method of pain scoring.…”
Section: Topical Anesthesiamentioning
confidence: 99%
“…Many studies found a decreased ''Premature Infant Pain Profile'' scores after instillation of topical anesthetic proparacaine 0.5% eye drops and supported the use of it during eye examinations of premature babies, which marginally decreases pain without any adverse effects. 12 The frequency of BP was still high after instillation of topical anesthetic in the current study.…”
Section: A Significant Challenge During Retinopathy Of Prematurity Scmentioning
confidence: 68%
“…Anesthetic eye drops partially minimize the pain caused by eyelid speculum insertion, scleral indentation and the bright light of the binocular indirect ophthalmoscope during the eye exam for ROP (7,19,20). However, even with the use of anesthetic eye drops, pain is still present during the eye exam.…”
Section: Discussionmentioning
confidence: 99%